Customer Awareness and Expectation Toward MY.Telkomsel.com Website - Shafira, Annisa; Aldianto, Leo (Journal of Business and Management, 2014)
Telkomsel is the first and the largest GSM mobile telecommunication operator in Indonesia. Tohelp its customers, Telkomsel has Grapari as walk in customer service and https://my.telkomsel.com as online customer service. In every day, Grapari always filled by the customer. Existence of my.telkomsel.com has not been able to reduce the amount of density that occurs in Grapari. It would be better if Telkomsel know how much the customers awareness about this MyTelkomsel website, what customers expect from this online customer service, and what kind of promotion can attract their attention.The conclusion of this research is actually there are many customers who aware of my.telkomsel.com as an online customer service from Telkomsel. But Simpati and Kartu As customers who use this website is much lesser than the actives of them. The customers expect that my.telkomsel.com have some features, such as changing and upgrading package limit easier, can buypulse, and can block number. Holding event that invites band/singer and promotions via SMS are the most effective communication for Telkomsel’s customers. By adding the expected features and doing the promotions that can attract the attention of customers, will make my.telkomsel.com better known and there will be more customers are using it.Keywords: Service Innovation, Customer awareness and expectation, Online customer service, Communication, Promotion.